2006
DOI: 10.1159/000089144
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of the Uterine Structure after Myomectomy

Abstract: Myomectomy is a good indication for women with uterine leiomyoma who desire to preserve their child-bearing potential. However, there are still no reports about how long it takes the uterus to reach a stable state after myomectomy. We evaluated the changes in uterine structure during the recovery process after myomectomy by MR images. MR images were used to analyze the time-dependant changes in the length of the uterine cavity, the volume of the uterus, recovery of the junctional zone, prevalence of modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 31 publications
0
29
1
2
Order By: Relevance
“…Magnetic resonance imaging (MRI) after myomectomy suggests the uterine healing takes at least 12 weeks and even longer if there is hematoma formation in the myometrium. 16 This study included only patients in whom single intramural myomas were removed. It seems logical that, if multiple myomas are removed with a greater propensity to myometrial hematoma formation, more time will be required before attempting pregnancy.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) after myomectomy suggests the uterine healing takes at least 12 weeks and even longer if there is hematoma formation in the myometrium. 16 This study included only patients in whom single intramural myomas were removed. It seems logical that, if multiple myomas are removed with a greater propensity to myometrial hematoma formation, more time will be required before attempting pregnancy.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…Findings from magnetic resonance imaging (MRI) studies after myomectomy suggests approximately 12 weeks preconception is required for uterine healing to occur and even longer if there is evidence of hematoma formation in the myometrium. 38 Hence, a 12-week waiting period is suggested before attempting pregnancy. If there a significant myometrial defect is created during the procedure, cesarean delivery is often recommended with a view to reduce the risk of uterine rupture during labor and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…If there a significant myometrial defect is created during the procedure, cesarean delivery is often recommended with a view to reduce the risk of uterine rupture during labor and delivery. 38 Of the patients who became pregnancy and delivered, 46.1% underwent cesarean section, the majority of which were elective or recommended by their obstetrician given their history of myomectomy. Prior studies have reported a post-RALM cesarean section rate of 95.7% and a wide range of cesarean section rates after laparoscopic myomectomy (23.5% to 82.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluating enucleated wounds after myomectomy have reported the utility of diagnostic imaging such as ultrasound and MRI for observing the temporal process of wound healing after myomectomy (14–17). As was done in the present study, these reports observed the myomectomy enucleation site at a second surgery.…”
Section: Discussionmentioning
confidence: 99%